Editorial: Digital systems supporting cognition and exploratory learning in 21st century - Sampson, Demetrios; Ifenthaler, D.; Isaias, P.; Spector, J. (Hong Kong Bao Long Accounting And Secretarial Limited, 2014)
Digital systems and digital technologies are globally investigated for their potential to transform learning and teaching towards offering unique learning experiences to the 21st century learners. This Special Issue on Digital Systems supporting Cognition and Exploratory Learning in 21st Century aims to contribute to the dialogue between the educational technology and educational psychology research community and the educational practitioners on current issues towards large scale take-up of educational technology. © 2014 Knowledge Management & E-Learning.